2019
DOI: 10.1159/000502261
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Modulation in Chronic Obstructive Pulmonary Disease: Current Concepts and Future Strategies

Abstract: Chronic obstructive pulmonary disease (COPD) is caused by the chronic inhalation of toxic particles and gases that are primarily but not exclusively derived from cigarette smoke that may be either actively or passively inhaled, which initiates a persistent innate and adaptive immune response in the lung. This immune response is associated with an aberrant tissue repair and remodeling process that results in varying degrees of chronic inflammation with excess production of mucus in the central airways and perma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 134 publications
(154 reference statements)
0
9
0
Order By: Relevance
“…A previous study reported that hypoalbuminemia is a potent, dose-dependent predictor of poor outcomes for pneumonia with COVID-19 infection [ 12 ]. An elevated level of CRP may be associated with the inflammatory response and cytokine storms caused by SARS-CoV-2 in the blood vessels [ 13 ]. These results were consistent with a previous study, which showed that the CRP level was positively correlated with the pneumonia severity [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that hypoalbuminemia is a potent, dose-dependent predictor of poor outcomes for pneumonia with COVID-19 infection [ 12 ]. An elevated level of CRP may be associated with the inflammatory response and cytokine storms caused by SARS-CoV-2 in the blood vessels [ 13 ]. These results were consistent with a previous study, which showed that the CRP level was positively correlated with the pneumonia severity [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most patients, COPD is characterized by T-helper 1 (Th1) and Th17-polarized inflammation, with local production of interferon (IFN)γ, tumor necrosis factor (TNF)α, interleukin (IL)-1b, IL-8, and other cytokines [20, 27, 28]. These recruit neutrophils, M1-polarized macrophages, and cytotoxic T cells, whose reactive oxygen species not only destruct the extracellular matrix to cause emphysema [29], but also aggravate smoking-induced DNA damage to initiate tumorigenesis in bronchial and alveolar epithelial cells (Fig.…”
Section: Immunopathogenesis Of Lung Cancermentioning
confidence: 99%
“…The inflammatory response and cytokine storms caused by SARS-CoV-2 in the blood vessels lead to an increased level of CRP [52] .This is in accordance with previous studies, which showed that the CRP level was positively correlated with the pneumonia severity [53] .Our data showed CRP values in COVID – 19 patients in the FVP therapy arm (106.03 ± 85.58) is much less than the control arm without FVP treatment (170.55 ± 282.69); P=0.016. However, a study by Mortaz et al [54] , on the effect of antiviral therapy (FVP or Kaletra) for 7 days on COVID-19 infected individuals showed a significant elevation in serum levels of IL-8 in non-ICU patients and TNFα, IL-1β, and IL-6 in ICU patients.…”
Section: Discussionmentioning
confidence: 99%